Contact Angle, Wettability and Adhesion. - Mittal, Kashmiri L. (Contact Angle, Wettability and Adhesion, 5., 2008)
This volume chronicles the proceedings of the 5th International Symposium on Contact Angle, Wettability and Adhesion Toronto, Canada, June 2006. Wettability is of pivotal importance in many and varied arenas, ranging from mundane to micro-and nanofluidics to lithography to biomedical. It should be underscored that in the last years there has been burgeoning interest in replicating the so-called "Lotus Leaf Effect" to create superhydrophobic surfaces. This volume contains a total of 19 papers covering many facets of contact angle, wettability and adhesion. All manuscripts were rigorou.